Tax Identification Socialization Media Application Ã¢â‚¬Å“Aku Tau Pajak SekarangÃ¢â‚¬Â Based on Android - Mentari, Mentari; Mulwinda, Anggraini (Journal of Vocational and Career Education, 2020)
Socialization in the form of games or educational games will be more interesting and fun. In addition, the use of applications on smartphones can indeed be a practical alternative to increase the ability to adapt to the surrounding environment and current developments. The purpose of this research is to build a tax introduction application "Aku Tau Pajak Sekarang" as a media of socialization. The application development method used is the Waterfall method. The steps of this research are communication, planning, modeling, construction, and deployment. In application testing, it is carried out by material testing, gain test, media test, and software feasibility test (functional suitability, compatibility, and usability). This research resulted in the application Ã¢â‚¬Å“Aku Tau Pajak SekarangÃ¢â‚¬Â which contains educational games that can be used as a media for socializing tax introduction. From the results of tests carried out, the application can be categorized as "very good" so that the application can be declared fit for use. The result of the material test got a percentage of 91.67%, the gain test got a score of 0.3409, the media test got a percentage of 97.5%, the functional suitability shows that the application can be used properly and there are no errors, compatibility shows a percentage of 100%, usability gets a percentage 80.33%.